2.8k views
2 votes
-x + y=-7
-3x - y = -5

User Bignose
by
4.9k points

2 Answers

5 votes

Answer:

y = -4, x = 3

Explanation:

-x + y = -7

-3x - y = -5

Isolate x for -x + y = -7.

-x + y = -7

Subtract y from both sides.

-x + y - y = -7 - y

Simplify.

-x = -7 - y

Divide both sides by -1


(-x)/(-1) =-(7)/(-1) -(y)/(-1)


(-x)/(-1)

Apply the fraction rule:
(-a)/(-b) =(a)/(b)


=(x)/(1)

Apply rule:
(a)/(1) =a


=x

Simplify
-(7)/(-1) -(y)/(-1)


-(7)/(-1) -(y)/(-1)

Apply rule:
(a)/(c) ±(b)/(c) =(a±b)/(c)


=-(7)/(-1) -(y)/(-1)

Apply the fraction rule:
(a)/(-b) =-(a)/(b)


=(-7-y)/(1)

Apply rule:
(a)/(1) =a


=-(-y-7)

Distribute parentheses.


=-(-7)-(-y)

Apply minus - plus rule.


-(-a)=a


=7+y


x=7+y

Substitute
x=7+y


[-3(7+y)-y=-5]

Isolate y for
-3(7+y)-y=-5


-3(7+y)-y=-5

Expand -3 (7 + y )

-3 (7 + y )

Apply the distributive law:
a(b+c)= ab+ac


a=-3,b=7, c=y


=-3*7+(-3)y

Apply minus - plus rule


+(-a)=-a


=-3*7-3y

Multiply the numbers: 3 * 7 = 21


=-21-3y


-21-3y-y=-5

Add similar elements:
-3-y=-4y


-21-4y=-5

Add 21 to both sides.


-21-4y+21=-5+21

Simplify.


-4y=16\

Divide both sides by -4


(-4y)/(-4) =(16)/(-4)

Simplify
(-4y)/(-4) =(16)/(-4)

Simplify
(-4y)/(-4)

Apply the fraction rule:
(-a)/(-b)=-(a)/(b)


=-(16)/(4)

Divide the numbers:
(16)/(4) =4

= - 4

y = -4

For x = 7 + y, substitute y = -4

x = 7 - 4

Subtract the numbers: 7 - 4 = 3

= 3

x = 3

y = -4, x = 3


(3,-4)

User Tony Wong
by
4.3k points
2 votes

Answer: x= - 3; y = -4

Explanation:

-x + y = -7

-3x - y = -5

-4x = -12

x= -12 /- 4

x= - 3

-x + y = -7

-(-3) + y = - 7

3 + y = - 7

y = - 7 + 3

y = -4

-x + y = -7

-3 - 4 = - 7

- 7 = - 7

User Jenjis
by
5.1k points